2014
DOI: 10.1051/e3sconf/20140301006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Variables Influencing Tenant Affordability to Pay Rent in Ipoh City Council Public Housing

Abstract: Abstract. Affordability reflects the challenges faced by households in balancing the real cost of housing and non housing expenditures against income limitations placed upon the household. Various methods have been introduced to measure housing affordability among households. This study was undertaken to identify the variables influencing tenant affordability to pay rent. Data was obtained through questionnaire distribution on 350 MBI public housing tenants using the strata sampling technique. This study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Furthermore, property attribute was found to have a positive and significant relationship with purchase intention of high-rise properties. It revealed that property attribute such as selling price, age of building, built-in furnishings and property land title may influence Malaysian purchasers' intention towards high-rise properties which is in line with other studies [3,17,28,29]. The findings of this study provide some significant business insight to property developers such as the likely influence of the buyer's positive attitude towards high-rise properties that showed a much greater influence towards the purchase intention compare to perceived behavioural control and property attributes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, property attribute was found to have a positive and significant relationship with purchase intention of high-rise properties. It revealed that property attribute such as selling price, age of building, built-in furnishings and property land title may influence Malaysian purchasers' intention towards high-rise properties which is in line with other studies [3,17,28,29]. The findings of this study provide some significant business insight to property developers such as the likely influence of the buyer's positive attitude towards high-rise properties that showed a much greater influence towards the purchase intention compare to perceived behavioural control and property attributes.…”
Section: Discussionsupporting
confidence: 87%
“…Besides, the view of high-rise property also played an important role in buyers purchase intention. According to Sew & Chin [16], the increasing in demand for housing located at hilly area are due to the natural beauty, impressive view, beautiful scenery, fresh air, and exclusiveness [17]. The hilly and sloppy terrain impressive views and good ventilation combined with the designer's architecture creativity will make hillside property attractive and exclusive which contributes to the increment of property value of the hillside property [17].…”
Section: A Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…HH size has a direct relationship with housing affordability in many aspects. On one hand the increase in HH size tends to increase the earning members, (Salleh et al, 2014) which in turn adds to the income of household leading to rise in affordability and increases the housing and non-housing expense, which tend to lower the affordability . Increase in HH size raises the housing demand and desire for house ownership and need for extra housing.…”
Section: Discussionmentioning
confidence: 99%
“…A good housing location consists of accessible public facilities (i-e education, health, park) proximity to workplace, public transport, and a healthy living environment. Whereby due to high cost of housing the poor get pushed to find housing in suburb of cities away, from workplace/social network, lacking public facilities, mostly slums/informal settlements (Salleh, et. al., 2014).…”
Section: Land Cost and Locational Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation